2002
DOI: 10.1142/s1088424602000270
|View full text |Cite
|
Sign up to set email alerts
|

Excited state dynamics in phthalocyanines studied using degenerate four wave mixing with incoherent light

Abstract: We present our experimental results on the measurements of excited state dynamics in phthalocyanines ( Pc , CuPc , FePc , and ZnPc ) using degenerate four wave mixing with incoherent light (DFWM-IL). Three different timescales were observed, for all samples, in the phase conjugate signal recorded as a function of delay in probe beam in the standard backward geometry. The fastest component (< 170 fs) is associated to the phase relaxation in the S n states and the slowest components (∼3-5 ps and 35-55 ps) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 22 publications
(37 reference statements)
3
46
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Several groups have argued about nuances of these materials in extensive range of photonic applications. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Our comprehensive experiments and detailed modeling, along with the obtained nonlinear coefficients, strongly suggest that these molecules are potential molecules with large nonlinear coefficients in ns, ps, and fs time domains with ultrafast response times.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Several groups have argued about nuances of these materials in extensive range of photonic applications. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Our comprehensive experiments and detailed modeling, along with the obtained nonlinear coefficients, strongly suggest that these molecules are potential molecules with large nonlinear coefficients in ns, ps, and fs time domains with ultrafast response times.…”
Section: Introductionmentioning
confidence: 99%
“…The high stability and capability of phthalocyanines, especially, to accommodate different metal ions within their cavity result in diverse optical properties. Even though nonlinear optical properties of surplus of phthalocyanines and their derivatives [11][12][13][14][15][16][17][18][19][20][21][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] have been investigated till date to assess their performance for NLO applications there remains further scope for investigation of novel structures with superior figures of merit. The best optical limiting performance till date has been achieved using a phthalocyanine in tandem with another nonlinear optical material justifies the potential of these molecules [56].…”
Section: Introductionmentioning
confidence: 99%
“…Using degenerate four-wave mixing with incoherent light, Rao et al found three different time components [135], which were assigned to phase relaxation of S n states (<170 fs), vibrational relaxation (∼3-5 ps), and population relaxation from the S 1 to the ground state (35 ps). Again, such a fast relaxation from S 1 is unrealistic, considering the known fluorescence quantum yield and lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies on the photophysics of ZnPc and similar compounds (derivatives or different metallophthalocyanines) in solution have been reported [130][131][132][133][134][135][136][137][138][139][140][141], but so far the results fail to depict a coherent picture of the overall photophysics. The generally accepted energy-flow model includes three major intramolecular relaxation pathways from the initially excited S 1 state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation